2023
DOI: 10.3390/coatings13091614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of WC Content on the Wear and Corrosion Properties of Oscillating Laser-Cladding-Produced Nickel-Based Coating

Xuening Li,
Songyan Zhang,
Wei Liu
et al.

Abstract: Pneumatic conveying pipe is an important part of the coal industry. Its working environment is harsh, and it is mainly affected by serious wear and corrosion, which affects its operating life. Studying a method of strengthening the pipe wall of pneumatic conveying pipe is of great significance. In this paper, nickel-based alloy coatings with different WC (tungsten carbide) contents were prepared using an oscillating laser-cladding process, and the micro-characterization characteristics, wear resistance and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The processing of the resulting coating by Deng et al [17] showed that NbC by increasing the coating hardness, GNP by lowering the COF, and the solidification process caused by laser cladding by creating refined grains significantly increase the wear resistance of the coating. Li et al [18] increased the wear and corrosion resistance of the pneumatic transmission pipe used in the coal industry using the Ni alloy-WC composite coating using laser cladding. Their report showed that expansion of equiaxed grains in the coating, reduction in the temperature gradient, and increase in hardness caused by the presence of WC are the most important reasons for resistance to wear and corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…The processing of the resulting coating by Deng et al [17] showed that NbC by increasing the coating hardness, GNP by lowering the COF, and the solidification process caused by laser cladding by creating refined grains significantly increase the wear resistance of the coating. Li et al [18] increased the wear and corrosion resistance of the pneumatic transmission pipe used in the coal industry using the Ni alloy-WC composite coating using laser cladding. Their report showed that expansion of equiaxed grains in the coating, reduction in the temperature gradient, and increase in hardness caused by the presence of WC are the most important reasons for resistance to wear and corrosion.…”
Section: Introductionmentioning
confidence: 99%